Mobility, sociability and wellbeing of urban living. - (:unkn) unknown (Springer, 2016)
This book investigates critical urban issues related to socio-spatial segregation, housing, daily travel, mobility of the elderly, etc. from the perspective of wellbeing. This is a collection of the latest research works by frontline researchers working in the fields of geography, urban studies, transport, and sociology. Drawing on theoretical and empirical explorations, collected chapters in this book connect mobility and wellbeing, bridge geography and health, and analyze the implications of mobility disadvantages on urban marginal groups' wellbeing. Research findings presented in the book are also highly relevant for practitioners and policy makers in the pursuit of improving urban livability since wellbeing, or quality of life, is increasingly considered as an important criteria alternative to income growth to evaluate economic, social and urban development.
Keywords: Stadtsoziologie; Arbeitsmigration; Wohnstandort; Nachbarschaft; Lebensbedingungen; Segregation; Stadtbewohner; Marginalität; Benachteiligung; Alltagsleben; Wanderarbeiter